Teamwork in a pandemic: insights from management research. Issue 2 (6th May 2020) - Mayo, Anna T
Abstract : Background: Amidst the unprecedented outbreak of COVID-19, it is both critical and increasingly difficult for healthcare professionals to engage in the teamwork that will underlie an effective response to the pandemic. The simultaneous need for and challenge to teamwork, though, is not unique to healthcare. Results: Drawing on management and organisational research conducted in healthcare as well as other industries, this article offers an overview of key, and robust, findings that highlight both what teamwork looks like and how to achieve it. I focus on two aspects of teamwork (the coordination of expertise and communication), and I review how leaders can jumpstart them by leveraging mechanisms including framing the work, using communication structures and engaging in leader inclusiveness.